2011
DOI: 10.7182/prtr.21.3.7kq304t4680wgh06
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative factors as predictors of blood product transfusion requirements in orthotopic liver transplantation

Abstract: Mean blood loss was 54.2 (SD, 47.9) mL/kg, the mean (SD) for amounts of blood products transfused was 25.3 (19.5) mL/kg for packed red blood cells, 2.6 (3.3) units for fresh frozen plasma, and 1.7 (3.1) units for platelets. Seven recipients (2.7%) underwent transplantation without intraoperative transfusion of red blood cells, whereas 25 patients (9.6%) received more than 10 units of red blood cells intraoperatively. Multivariable analysis showed that no preoperative factor was a predictor of blood loss or req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Traditionally, liver transplant recipients are considered to be in a hypocoagulable state, as evidenced by abnormalities in routine hemostatic tests such as the PT and platelet count and massive perioperative transfusion requirements . This conflicts, however, with the trend of transfusion‐free liver transplant procedures and the finding that prolonged PT and APTT or thrombocytopenia does not correlate with the amount of intraoperative blood loss . With the emergence of the concept of rebalanced hemostasis, there is an increasing awareness of perioperative thrombotic complications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Traditionally, liver transplant recipients are considered to be in a hypocoagulable state, as evidenced by abnormalities in routine hemostatic tests such as the PT and platelet count and massive perioperative transfusion requirements . This conflicts, however, with the trend of transfusion‐free liver transplant procedures and the finding that prolonged PT and APTT or thrombocytopenia does not correlate with the amount of intraoperative blood loss . With the emergence of the concept of rebalanced hemostasis, there is an increasing awareness of perioperative thrombotic complications.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were also reported from a high‐volume Korean LDLT center and for deceased donor liver transplantation . This tendency was also confirmed in our study, but in contrast to our results, previous studies found no possible association between preoperative coagulopathy and postoperative hemorrhaging . Our results clearly demonstrated that the more severe the liver disease was, the higher the incidence of hemorrhagic complications was.…”
Section: Discussionmentioning
confidence: 99%
“…Higher cMELD scores may indicate worse residual liver functions, and could be associated with susceptibility to coagulopathy. However, conflicting results have been reported regarding the association between cMELD score and blood transfusion in OLT [41,42,[44][45][46][47][48][49][50]. It was not always specified in these studies whether cMELD score was separated from its components for the multivariate analysis.…”
Section: Discussionmentioning
confidence: 90%
“…>1 blood volume in 24 h) . Towards the turn of the century, significantly lower utilization rates were reported, but there was still significant interinstitutional variation and apparently large standard deviation within institutions . Given this variation, different programmes need varying standard amounts of blood products available prior to a liver transplant that can result in ineffective utilization of a vital resource.…”
Section: Introductionmentioning
confidence: 99%